KINERJA PENGENDALIAN HAMA PADI SAWAH PASCA INTRODUKSI TEKNOLOGI PENGENDALIAN HAMA TERPADU - ADE SUPRIATNA; IKIN SADIKIN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
This study was conducted in 1998 and took place in Karawang as center of WestJava's rice production and as representation of rice farm in Java’s north coast. The objectivesof study were to describe the appearance of the farmer in controlling pest after introducingIntegrated Pest Management (IPM) technology, to analyze the cost of pest control and itseffect on both production and in come, and to measure the pesticide residues in grain as afinal product. The result showed that some components of IPM technology as preventiveagainst the pest exploding have adopted by the farmers. Forty eight percent of the farmershave applied the insecticide based on IPM concept. The cost of pest control was Rp.94,000(9% of total cost) consisting of pesticide cost (64%) and applying cost (36%)/ha/season. Thenumber of pesticide applied by the Non IPMT farmer was higher than that of IPMT farmerbut they did not influence to production and in come. The result of chemical analysis showedthat some pesticide residues have pound but their concentration were still under MaximumResidue Limits (MRL) namely BPMC and endosulfan. The others were not detected such assipermetrin, deltametrin, monocrotophos, diazinon, carbopuran, calbaril, etc. because theirconcentration was still too low. Nevertheless, the residues of undegradable pesticide appliedby the farmer in the past time have still found namely aldrin and DDT.